2015
DOI: 10.3727/096368914x685087
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal Stem Cells Overexpressing Angiotensin-Converting Enzyme 2 Rescue Lipopolysaccharide-Induced Lung Injury

Abstract: Bone marrow-derived mesenchymal stem cells (MSCs), which have beneficial effects in acute lung injury (ALI), can serve as a vehicle for gene therapy. Angiotensin-converting enzyme 2 (ACE2), a counterregulatory enzyme of ACE that degrades angiotensin (Ang) II into Ang 1-7, has a protective role against ALI. Because ACE2 expression is severely reduced in the injured lung, a therapy targeted to improve ACE2 expression in lung might attenuate ALI. We hypothesized that MSCs overexpressing ACE2 would have further be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
79
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 90 publications
(89 citation statements)
references
References 46 publications
(73 reference statements)
7
79
0
Order By: Relevance
“…A pathologist, blinded to the identity of the slides, used a light microscope to evaluate lung injury scores according to the following five criteria: edema, alveolar and interstitial inflammation, alveolar and interstitial hemorrhage, atelectasis, and hyaline membrane formation. 21 …”
Section: Measurement Of Evans Blue Leakagementioning
confidence: 97%
“…A pathologist, blinded to the identity of the slides, used a light microscope to evaluate lung injury scores according to the following five criteria: edema, alveolar and interstitial inflammation, alveolar and interstitial hemorrhage, atelectasis, and hyaline membrane formation. 21 …”
Section: Measurement Of Evans Blue Leakagementioning
confidence: 97%
“…MSCs are capable of homing to and acting as a vehicle for delivery of protective genes to the injury site, which may not only enhance their therapeutic effects but also promote local lung repair [20]. Delivery of a protective gene by MSCs can overcome the limitations of transient gene expression, host immunoinflammatory responses, and nonspecific cell targeting by classic viral or nonviral vectors [46]. Therefore, we chose BM-MSCs as the vehicle to upregulate HO-1 expression in an LPS-induced inflammatory microenvironment.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms of MSC protection against ALI/ARDS include multilineage differentiation potential (e.g., cell replacement and tissue regeneration), paracrine (e.g., secretion of antimicrobial and repair factors), and cell-cell contactdependent (e.g., transfer of nucleic acids and organelles) mechanisms [17]. Currently, it is believed that paracrine activity plays a predominant role in the therapeutic effects of MSCs [46]. MSCs have the ability to release multiple soluble factors, such as growth factors, antiinflammatory cytokines, and antimicrobial peptides, which can improve endothelial and epithelial permeability, modulate innate and adaptive immunity, and protect against oxidative damage-induced apoptosis [50].…”
Section: Discussionmentioning
confidence: 99%
“…In the pathogenesis of ALI, inflammation and the development of lung tissue damage results in large part from the mobilization of inflammatory cells by cytokines. Evidence has demonstrated that the renin‐angiotensin system involved in the pathophysiology of ARDS and ALI results in increased production of angiotensin II (Ang II) . The mediators that promote inflammation might also be the same molecules that attract MSCs to the site of tissue injury.…”
Section: Introductionmentioning
confidence: 99%